ACSM's resources for the exercise physiologist a practical guide for the health fitness professional - Magyari, Peter; Lite, Randi; Kilpatrick, Marcus; Schoffstall, James; American College of Sports Medicine (Philadelphia Wolters Kluwer Health, 2018)
"Provide the most current, competent guidance to your clients and success on the exam with this official preparation book for the ACSM Certified Exercise Physiologist examination. Reflecting key changes of the Tenth Edition of ACSM's Guidelines for Exercise Testing and Prescription, this Second Edition includes the new per-participation guidelines, incorporates ACSM's Exercise is Medicine global health initiative throughout, and offers up-to-date coverage of the full scope of ACSM EP-C practice domains, including the information you need to provide effective program options for both healthy and special populations." -- Back cover
Understanding physical activity and exercise -- Preparticipation physical activity screening guidelines -- Cardiorespiratory fitness assessments and exercise programming for apparently healthy participants -- Muscular strength and muscular endurance assessments and exercise programming for apparently healthy participants -- Flexibility assessments and exercise programming for apparently healthy participants -- Functional movement assessments and exercise programming for apparently healthy participants -- Body composition and weight management -- Exercise for individuals with controlled cardiovascular, pulmonary, and metabolic diseases -- Exercise programming for individuals with musculoskeletal limitations -- Exercise programming across the lifespan : children and adolescents, pregnant women, and older adults -- Theories of behavior change -- Facilitating health behavior change -- Healthy stress management -- Legal structure and terminology -- Leadership and management -- General health fitness management -- Marketing -- Professional behaviors and ethics.
Includes bibliographical references and index.
Keywords: Exercise Therapy; Exercise -- Physiological aspects; Sports Medicine